Resonant Energy Transfer-Mediated Efficient Hole Transfer in the Ternary Blend Organic Solar Cells - Yadav, Suraj; Shivanna, Ravichandran; Mohapatra, Aiswarya Abhisek; Sawhney, Nipun; Gangadharappa, Chandrasekhar; Swaraj, Sufal; Rao, Akshay; Friend, Richard H.; Patil, Satish (The journal of physical chemistry letters, 2023)
The ternary blend approach accomplished improved spectral coverage and enhanced the power conversion efficiency (PCE) of organic solar cells (OSCs). However, the role of the third component in improving the photovoltaic parameters needs critical analysis. Here, we introduced a wide band gap n-type twisted perylene diimide (TPDI) into the PM6:Y6 blend as a third component that improves spectral coverage and morphology, resulting in an overall increase in the efficiency of the OSCs. TPDI acts as an antenna for efficient energy- and charge-transfer processes. A systematic study compared charge- and energy-transfer dynamics and the orientational dependence nanomorphology of ternary blends with those of their binary counterparts. Femtosecond transient absorption measurements reveal enhanced hole-transfer efficiency in finely tuned ternary mixtures. This study provides a rational approach to identifying a third component to improve light management and morphology. These parameters enhance the energy and charge-transfer processes, improving the PCE of OSCs.